Solar energy available and energy generated in photovoltaic systems in different inclinations and orientations of roofs of buildings (Research, Society and Development, 2021)
This work aimed to determine the solar energy available in different inclinations and orientations of roofs of buildings in the four seasons, using data of Global Solar Irradiation in the horizontal plane, temperatures, and wind speed. The inclined hourly solar irradiation and the energy generated by photovoltaic systems of different capacities installed in Cascavel-PR were simulated, with different orientations and inclinations and types of roofs (ceramic, fiber cement and metal). SWERA (Solar and Wind Energy Resource Assessment) daily global solar irradiation and wind velocity data were used to simulate daily inclined global solar irradiation in PVSyst software. Thus, also with the help of the software, the energy generated by photovoltaic systems of different capacities installed in Cascavel - PR, with different orientations and inclinations of roofs was determined. Consequently, the levels of losses in different seasons of the year were calculated and an analysis of the economic viability of the undertakings was made. Thus, the losses, profits and income of the systems were compared. Solar panels installed in northern oriented ceramic roofs provide better energy production performance throughout the year compared to metallic roofs and fibrocement. However, for the other orientations (South, East and West), the losses for ceramic roofs were twice as high as the metallic and fibrocement roofs in relation to their respective northern orientated slopes. Regarding orientation, roofs oriented to the North receive more Irradiation annually and therefore produce more energy. Then there is East, West and South as the most unfavorable condition.